2021
DOI: 10.11646/phytotaxa.513.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Polygala guilanica (Polygalaceae), a new species from Guilan Province, N Iran

Abstract: A new species, Polygala guilanica (Polygalaceae), is described from Kooh-Roubar, Gasht-Roodkhan protected area in W Guilan province, N Iran. The new species is distinguished based on its prostrate stem; small, lanceolate, ovate and rhombic, sessile leaves; tiny pink-white flowers in lax terminal racemes; 6 or 8 stamens with sessile anthers, a filiform style and brownish seed with 3-lobed caruncle. Detailed morphological description of the new species, photographs and distribution map are provided. Polygala gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…After careful comparison of morphological characters in living and herbarium specimens (CALI), and after consulting relevant literature (Adema 1966;Chandrabose & Nair 1981;Banerjee 1993;Banerjee & Balakrishnan 2005;Chen & al. 2008;Ranjan 2009;Kerrigan 2008Kerrigan , 2012Yang & Chen 2013;Dönmez & Aydin 2018;Pastore 2018aPastore , 2018bSarvi & al. 2020;Ying 2020;Pastore & al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After careful comparison of morphological characters in living and herbarium specimens (CALI), and after consulting relevant literature (Adema 1966;Chandrabose & Nair 1981;Banerjee 1993;Banerjee & Balakrishnan 2005;Chen & al. 2008;Ranjan 2009;Kerrigan 2008Kerrigan , 2012Yang & Chen 2013;Dönmez & Aydin 2018;Pastore 2018aPastore , 2018bSarvi & al. 2020;Ying 2020;Pastore & al.…”
Section: Introductionmentioning
confidence: 99%
“…2021aPastore & al. , 2021bPastore & Antar 2021;Sarvi & al. 2021;Pastore 2022) we found that the entity in question is consistently distinct from all other species of the genus and is described here as new.…”
Section: Introductionmentioning
confidence: 99%